POTENSI LANSKAPKAWASAN PERKAMPUNGAN TLOGOMAS KOTA MALANG - Kota, Wilhelmina Medho; Sutoyo, Sutoyo; Astutik, Astutik (Fakultas Pertanian, 2012)
Green open spaceis dominated by plants which are producers of oxygen (O2) and the ecology cycle stabilizer. Green open space function sustain ecology as balance to city ecosystem.Developmentof the city with uncontrolled population growth tends to change the natural landscape thereby reducing the area of green open space. Green open space is reduced to reduce environmental qualities city residents. Therefore, it takes the role of goverment and increase comfortable and aesthetic area. The study aims ; 1) to knowthe type and amount of vegetation, 2) to know the layout of vegetation,3) to createcool environment and free by air pollution in Tlogomas. The method used was a survey. Results showed Tlogomas Village Lowokwaru Malang City has the potential to support the creation of green open space. The type of vegetation totaling 55 types of vegetation are trees and shrubs. The dominant vegetation types is Bougenvil especlobilisi, Araceae, Orcidaceae, Aglaonema sp, Ceysaltheheum sp, Acaliphamicriphila, Euphorbia, rosa sp, Jasminum sp, Bonsai, and Araceae. The structureof landscape plants that served the aesthetic function of mass, continue, and linier along the way by using a variation of canopy shape, color, and texture of the leaves. The structuring plants grown horizontally along the way and the continuous linear shape. While plant height varied vertically to create an atmosphere of diversity